2020
DOI: 10.1111/rec.13154
|View full text |Cite
|
Sign up to set email alerts
|

Linking social identity, risk perception, and behavioral psychology to understand predator management by livestock producers

Abstract: Human behaviors can determine the success of efforts to restore predators to ecosystems. While behaviors such as lethal predator control may impede predator restoration, other land management practices can facilitate coexistence between predators and humans. Socio‐psychological theories provide useful tools for understanding and improving these human behaviors. We explore three frameworks to understand what shapes Australian livestock graziers' behaviors with regards to management of the threat that dingoes po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 70 publications
(88 reference statements)
0
12
0
Order By: Relevance
“…In a public survey, we found that Australians had limited awareness of dingo management, held negative attitudes toward lethal control of dingoes, and supported retaining dingoes as top predators in Australian ecosystems . This included similar (negative) attitudes toward lethal dingo control as those held toward killing kangaroos and horses (van Eeden, Newsome, et al, 2020;, so we might expect that public backlash against dingo control would have similar outcomes (i.e., restricting lethal control actions by governments) if public awareness about dingo management improves. Raising public awareness may lead to support for conservationists advocating policy change for dingo management.…”
Section: The Australian Publicmentioning
confidence: 99%
See 3 more Smart Citations
“…In a public survey, we found that Australians had limited awareness of dingo management, held negative attitudes toward lethal control of dingoes, and supported retaining dingoes as top predators in Australian ecosystems . This included similar (negative) attitudes toward lethal dingo control as those held toward killing kangaroos and horses (van Eeden, Newsome, et al, 2020;, so we might expect that public backlash against dingo control would have similar outcomes (i.e., restricting lethal control actions by governments) if public awareness about dingo management improves. Raising public awareness may lead to support for conservationists advocating policy change for dingo management.…”
Section: The Australian Publicmentioning
confidence: 99%
“…Our ToC aims to promote a more inclusive decision‐making process. Our assessment of the relevant contexts and stakeholders is largely informed by the results of the lead author's (LvE) interdisciplinary PhD research on the social, political, and historical factors that shape dingo management (van Eeden et al, 2018; van Eeden, Dickman, Crowther, & Newsome, 2019; van Eeden, Dickman, Newsome, & Crowther, 2019; van Eeden, Newsome, Crowther, Dickman, & Bruskotter, 2019; van Eeden, Newsome, Crowther, Dickman, & Bruskotter, 2020; van Eeden, Slagle, Crowther, Dickman, & Newsome, 2020; van Eeden, Smith, Crowther, Dickman, & Newsome, 2018), along with the expertise of the other three authors (CD, MC, TN) whose combined experience in research on dingo ecology and biology exceeds 49 years.…”
Section: Developing a Toc To Promote Coexistence With Dingoesmentioning
confidence: 99%
See 2 more Smart Citations
“…Wildlife conservation and the mitigation of human-wildlife conflict are increasingly recognized to be as much social as ecological challenges (Baruch-Mordo et al, 2009;Dickman, 2010), and predator conservation in particular requires promoting social tolerance (Chapron et al, 2014), especially in contexts where the recovery of predator populations is supported by human constituencies that are geographically removed while negative impacts are borne locally (Treves and Bruskotter, 2014;Lute and Carter, 2020). While much of the public in the United States supports the use of nonlethal tools to promote human-predator coexistence (Slagle, 2017), rural residents and ranchers may remain more likely to favor lethal removal (Dietsch et al, 2011;Treves et al, 2013;Responsive Management, 2019).…”
Section: Introductionmentioning
confidence: 99%